Childfree Sebagai Representasi Feminisme Radikal Istri Terhadap Suami: Childfree As A Representation Of Wives' Radical Feminism Towards Their Husbands - Ramadhani, Azifa Putri; Nina Yuliana (Lembaga Pengembangan Kinerja Dosen, 2024)
The Childfree phenomenon is increasingly becoming a trend in modern society in the 21st century. Childfree is a term used to refer to couples who do not want to have children during their marriage. There are different opinions and views regarding the presence of children in marriage, so that the phenomenon of not having children in society still has advantages and disadvantages. Children are believed to be God's gift and bring harmony to the family. Apart from that, religion also recommends having children. Because it brings great rewards. Therefore, children's freedom is still considered a bad thing. Views from several perspectives also think that not having children will allow a woman to maintain her beauty without having to experience aging, sagging skin or even wrinkles. This research was conducted to discuss the childfree phenomenon from the perspective of the subordinate Gita Savitri and the reasons why her husband did not fight back. This research uses a qualitative approach with data collection methods in the form of video analysis. This study shows not only men's powerlessness in running the family, but also the ability of women who have determination and strength to exercise control in the household.